Purification and characterization of S-adenosylhomocysteine deaminase from streptonigrin-producing Streptomyces flocculus. - Zulty, J J (1989)
An S-adenosylhomocysteine deaminase has been isolated and purified from streptonigrin-producing Streptomyces flocculus ATCC 13257. Deamination represents the major metabolic route of S-adenosylhomocysteine in this organism. The protein was found to be monomeric with a molecular weight of 56,100 +/- 1,600. The activity was optimal at pH 7.0 and 37 degrees C, and the deaminase was inactivated by p-chloromercuribenzoate but not by metal chelators. The Km for S-adenosylhomocysteine is 2.5 mM, and the Ki for inhibition by deoxycoformycin is 1.6 nM.